2008
DOI: 10.1128/jvi.01441-07
|View full text |Cite
|
Sign up to set email alerts
|

Rous Sarcoma Virus (RSV) Integration In Vivo: a CA Dinucleotide Is Not Required in U3, and RSV Linear DNA Does Not Autointegrate

Abstract: The sequences required for integration of retroviral DNA have been analyzed in vitro. However, the in vitro experiments do not agree on which sequences are required for integration: for example, whether or not the conserved CA dinucleotide in the 3 end of the viral DNA is required for normal integration. At least a portion of the problem is due to differences in the experimental conditions used in the in vitro assays. To avoid the issue of what experimental conditions to use, we took an in vivo approach. We ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…Because the effects on the relative titer are small (less than twofold), real-time PCR is not accurate enough to determine whether there is an effect on plus-strand DNA synthesis. We previously mutated the nucleotide at the 5Ј end of U3 and showed that altering this nucleotide did not affect the specificity of cleavage at the PPT-U3 junction (18). Taken together, our data suggest that the U3 sequences near the PPT-U3 junction do not make significant contributions to the specific cleavage at the PPT-U3 junction by the RNase H of RSV RT.…”
Section: Resultsmentioning
confidence: 68%
“…Because the effects on the relative titer are small (less than twofold), real-time PCR is not accurate enough to determine whether there is an effect on plus-strand DNA synthesis. We previously mutated the nucleotide at the 5Ј end of U3 and showed that altering this nucleotide did not affect the specificity of cleavage at the PPT-U3 junction (18). Taken together, our data suggest that the U3 sequences near the PPT-U3 junction do not make significant contributions to the specific cleavage at the PPT-U3 junction by the RNase H of RSV RT.…”
Section: Resultsmentioning
confidence: 68%
“…Host proteins within the preintegration complex of retroviruses serve to stimulate efficient intermolecular integration and suppress autointegration (44). The hallmarks of autointegration are the creation of 1-and 2-LTR circles with heterogeneity resulting from differences in the orientation of the intasome attack and the creation of junctions joining processed 5= and 3= LTRs to viral DNA (45). One can distinguish the 2-LTR circles that result from autointegration from "true" 2-LTR circles formed by end-to-end ligation by PCR amplification across the 2-LTR junction and gel analysis of the products.…”
Section: ) (B)mentioning
confidence: 99%
“…We wanted to test how aberrant U3 ends are treated by RSV IN and to ask whether a CA was required for the efficient integration of the U3 end. Full-length integrated viral DNAs were recovered from cells infected with these mutant viruses as described previously (18). Recovered plasmids were sequenced, and the chicken genomic sequences were analyzed by BLAT searches (http://genome .ucsc.edu/cgi-bin/hgBlat).…”
mentioning
confidence: 99%
“…When the aberrant virus/host junctions were examined, there were, in many cases, microhomologies involving one to nine nucleotides between the virus and host sequence (see Table S1 in the supplemental material). We previously showed that, at this type of aberrant junction, there frequently are microhomologies between the host and virus DNA (17,18). Given that the fraction of 2-LTR circle junctions with large deletions in the U3 sequences (these circles would arise from linear viral DNAs with large deletions in U3) was much lower in both mutants than in the wild type, the fact that infections with both viruses with U3 duplications led to the generation of proviruses in which there was a moderate fraction (20%) with defects at the U3 junction suggests that the last six nucleotides in U3 are sufficient to direct integration with moderate efficiency in vivo but that a larger segment makes contributions to efficient/accurate integration.…”
mentioning
confidence: 99%
See 1 more Smart Citation